Health-Care Systems Lessons from the Reform Experience - Docteur, Elizabeth (OECD Economics Department Working Papers, 2003)
This study reviews health-system reforms in OECD countries over the past several decades and their impact on the following policy goals: ensuring access to services; improving the quality of care and its outcomes; allocating an "appropriate" level of resources to health care (macroeconomic efficiency); and ensuring microeconomic efficiency in service provision. While nearly all OECD countries have achieved universal insurance coverage, initiatives to address persistent disparities in access are now being undertaken in a number of countries. In light of new evidence of serious problems with health-care quality, many countries have recently introduced reforms, but it is too soon to generalise as to the relative effects of alternative approaches. Instruments aimed at cost control have succeeded in slowing the growth of (particularly public) health-care spending over the 1980s and 1990s but health-care spending continues to rise as a share of GDP in most countries. A few countries have ...This paper is also published under OECD Health Working Papers Series